Petunjuk Alquran Tentang Belajar Dan Pembelajaran - Hamzah, Syeh Hawib (Dinamika Ilmu, 2009)
Al-qurâan is normative source in Islamic education. Al-qurâan consists of the importance of learning and study. Itâs described from many verses of Al-qurâan which explain about knowledge. For instance, the first verse that stated âiqraâ which is in Indonesian language means âbacalahâ. Furthermore, Al-qurâan contains the methods used in learning in order to ease people who want to study. Those kinds of methods are discussion method, tarhib wa targhib method, story method, learn by example method, and also practice and repeating method.